Produtividade de grãos e da água do milho sob diferentes níveis de adubação nitrogenada e densidade de plantas em ambiente irrigado e de sequeiro - Einsfeld, Viviann Yndiana (2024)
Water and nitrogen (N) availability are the main factors affecting biomass and grain production in maize cultivation. The lower N absorption of corn grown under rainfed conditions is due to lower demand resulting from lower growth of aboveground biomass and root system. Under irrigation conditions, high N rates can inhibit absorption due to mineralization, especially in areas with high organic matter content. Therefore, the main objective of this study was to evaluate the combined effect of nitrogen fertilization, water availability, and plant density on grain and water productivity in maize. Three experiments were carried out in the 2022/23 growing season: Santa Maria (SM), Cruz Alta (CA), and Boa Vista do Cadeado (BVC). In CA and BVC, the experimental design consisted of a randomized block in a bifactorial 2x4 scheme with four replications. Factor A consisted of two plant densities (7.0 and 8.5 plants m-2), while factor D consisted of four topdressing nitrogen rates (0, 75, 15,0 and 300 kg ha-1). In CA, the experiment was conducted under a central pivot irrigation system, while in BVC, the experiment was carried out in a rainfed environment. In SM, a three-factor DBC (2x2x4) was used, where factor A consists of irrigation management (irrigated and rainfed), factor C consists of plant densities, and factor D consists of N rates (as in CA and BVC experiments). The SIMDualKc model was used to simulate the soil water balance and consumption in different environments. The model was calibrated with the irrigation treatment of the SM experiment, 7.0 plants m-2, and 300 N rate. Soil water content was monitored using FDR sensors to a depth of 80 cm. The results showed a significant difference in grain yield for plant density factor in CA, with yields of 15.6 and 16.6 Mg ha-1 for populations of 7 and 8.5 pl m-2, respectively. In the rainfed condition, decreasing linear behavior was observed with increasing dose. Lower water availability reduced N absorption and demand, which was reflected in lower LAI and plant height. In SM, rainfed yield was 4.35 Mg ha-1compared to 3.6 Mg ha-1 in BVC. The lower yield for BVC is due to the water deficit that occurs during peak demand. Greater available soil water (ASW) and occasional rainfall during the grain-filling period favored the higher yield of rainfed corn in SM. The lack of responsiveness of corn yield to varying N rates in an irrigated environment may be related to mineralization and higher N losses through leaching. The SIMDualKc model adequately reproduced the observed ASW (available soil water) under the different growing conditions, with bo values ranging from 0.96 to 1.03, R2 between 0.89 and 1.0, and RMSE ranging from 3.2 to 12.10 mm, which represents less than 15% of the average observed ASW.